Climate Change & Its Effects on Human Health: A Comprehensive Review - Rizwan Arif; Neha Sahu (International Journal of Climate Conditions, 2024)
Anthropogenic climate change has wide-ranging effects on human health and is a significant worldwide concern. This thorough analysis highlights the connections between environmental, social, and biological elements as it explores the complex implications of climate change on health. Numerous health consequences, such as vector-borne infections, heat-related illnesses, respiratory issues, and mental health issues, can be impacted by shifting precipitation patterns, rising temperatures, and a rise in the frequency of extreme weather events. Children, the elderly, those living in low-income areas, and other vulnerable groups are disproportionately impacted. Furthermore, the exacerbation of pre-existing health inequities by climate change adds to the burden on global healthcare systems. Mitigation and adaptation strategies are essential to address these health impacts, requiring coordinated efforts from governments, healthcare providers, and communities. This review underscores the urgent need for integrated policies that prioritize public health in the context of a changing climate, fostering resilience and promoting sustainable development. Increased heat wave frequency and intensity, which results in heat-related illnesses and mortality, are among the direct health implications of climate change. In addition, when infectious disease vectors like mosquitoes broaden their geographic range, shifting weather patterns aid in the spread of infectious diseases. The review also explores the health implications of extreme weather events, such as hurricanes and floods, which can cause injuries, mental health disorders, and disruption of healthcare services. Moreover, climate change exacerbates air pollution, with significant respiratory and cardiovascular consequences. The health burden is further compounded by the displacement of populations brought about by extreme weather events and increasing sea levels, which increases the prevalence of waterborne illnesses, mental health disorders, and starvation in the impacted areas.
Keywords: Air quality; Extreme Weather events; Food security; Heat Waves; Human Health Impacts; Waterborne Diseases